Ragam Jenis Dan Kelimpahan Lalat Pada Peternakan Sapi Di Kupang - Lelita Antoh; Julianty Almet; Aji WINARSO (Jurnal Veteriner Nusantara, 2021)
East Nusa Tenggara (NTT) is one of the provincial livestock producer and breeder sector has also become one of the sectors that support the communities in the province of East Nusa Tenggara. In support of the program of cattle to be free of the disease, efforts to improve the beef cattle population is affected by several factors such as enclosure management and disease prevention. Diseases that can reduce productivity in cattle caused by bacteria, viruses, endoparasites and ectoparasites. One of the ectoparasites that act as vectors of disease that often occurs in cattle are flies. This study aims to look at the Variety type and abundance Flies On Cattle in Kupang located in two studies namely Cattle Farmers Group Noetnana, Village Fatukoa, District Maulafa, Kupang (farm I) and Cage Cattle SMK PP Kupang State (farm II). Fly collection is done by using two methods: the method of sweeping and manual methods.Flies sample processing is done by piercing flies (pinning) using pinning needles on one side of the thorax slightly to the right of the center line.The diversity of types of flies analyzed using the formula of relative abundance. The diversity of types of flies obtained during the research was Haematobia sp. Hippobosca sp. Stomoxys calcitrans, Musca domestica, and Tabanus sp. Factors that contributed to support the amount of diversity of types of flies are carrying appropriate for the survival of various types of flies in these locations such as temperature, humidity, food and breeding grounds. The total number of flies were obtained during the study was 3308 flies.